Simultaneous Presentation Of Both True And False Aneurysm In The Infrarenal Aorta. Issue 3 (1st October 2000) - Townend, M; Keightley, A; Price, B A
Abstract : Interventional radiology has resulted in a reduced need for bypass procedures for aorto-occlusive disease. However, there are still indications for surgery of this type, which carries with it a small but significant morbidity and mortality. False aneurysms are well described following such procedures but with the development of inert, strong and non-absorbable materials they are becoming less common. This paper describes the acute presentation of a false aneurysm of the aorta following an aorto-iliac bypass where true aneurysmal change had taken place in the area of the anastomosis.